Characterization of two novel HLA‐A null alleles: A*11:210N and A*26:107N. Issue 6 (7th April 2015) - Balas, A.; Sánchez‐Gordo, F.; García‐Sánchez, F.; Gómez‐Zumaquero, J. M.; Vicario, J. L.
<x xml:space="preserve">Abstract</x> Two new HLA‐A null alleles were characterized, A*11:210N and A*26:107N.